(untitled) (Future Cities and Environment, 2025)
The productivity of the business owner among women’s community in Madura currently was very weak and is expected to improve after the implementation of the our empowerment program. The research method used in this research is descriptive qualitative with primary data sources obtained from interviews. On this basis, this research was conducted to examine and formulate a community empowerment model that can be applied to increase the productivity of the Madurese community. The results of this research show that the women’s community in Madura who have businesses in the fields of food, crafts, clothing, batik and so on have generally adopted simple technosociopreneurship strategy. However, the this adopted strategy need to improve further. This could be because their emphasis in the technology sector is still limited to promotional and ordering activities only. In the future, what needs to be improved by the women’s community in Madura who have businesses is to try to develop their business management based on technology, starting from business management, sales systems to the recruitment system for members from the community who want to join to become dropshippers or franchise members. It is expected that this paper can start more comprehensive development of technosociopreneurship for the betterment of woman and community in the island.